Conservative treatment of breast cancer: modified irradiation technique for women with large breasts - Zierhut, Dietmar; Flentje, Michael; Frank, Claudia; Oetzel, Dieter; Wannenmacher, Michael (Radiotherapy and oncology, 1994)
Seven patients with large, pendulous breasts received external beam irradiation to the whole breast (50 Gy in 25 fractions plus boost) after lumpectomy. A special breast holding mask was shaped for each patient. Three-dimensional treatment plans and dose-volume histograms of the same patient with and without a mask were compared. Day-to-day variance was checked. This technique provides improvements in dose homogeneity, reproducibility, and sparing of normal tissues. Cosmetic outcome at present is good.
Elektronische Reproduktion der Druck-Ausgabe: 14. April 2005
Gesehen am 11.02.2025